“Bird in a Cage”: Traditions and Customs That Restrict Women’s Rights in the Kazakh Context as a Research Topic - Absatar, Aruzhan; Alishayeva, Botakoz (ETHICS IN PROGRESS, 2023)
Kazakh traditional wisdom says “Kaytyp kelgen kyz zhaman” - a girl who returns to her parental home after marriage is a disgrace to the family. According to a women’s rights organization, up to 5,000 bride kidnapping acts occur annually in contemporary Kazakhstan. The authors would like to approach this socio-cultural phenomenon through considering the current situation of women and their rights in Kazakhstan. The article examines how outdated traditions and customs violate women’s’ personal boundaries and rights in Kazakhstan. Its main purpose is to attract the attention of the reader and potential researcher and to familiarize them with the topic (a specific form of violence against women), research methods, and research challenges. Until September 2019, there was no special legislation in Kazakhstan aimed at combating domestic violence. However, with the adoption of the Law “On the Prevention of Domestic Violence and the Protection of Victims of Domestic Violence” in September 2019, Kazakhstan introduced institutional measures to prevent and punish domestic violence. Nevertheless, people continue to follow their traditional customs, rather than live in accordance with new legislation.